Electrostatic self-assembly deposition of layered calcium niobate intercalated with task-specific ionic liquid and its electrocatalytic activity - Yang, Min (2019)
A novel intercalation compound of Dion–Jacobson-type perovskite calcium niobate (KCa2Nb3O10) with the nitroxy radical 2,2,6,6-tetramethylpiperidyl-1-oxy (TEMPO) task-special ionic liquid (TEMPO-IL) has been successfully synthesized through a facile and rapid electrostatic self-assembly deposition (ESD) technique. The TEMPO-IL/Ca2Nb3O10 nanocomposite has been examined for the electrochemical detection of nitrite using cyclic voltammetry and differential pulse voltammetry techniques. The electrochemical studies demonstrate that TEMPO-IL/Ca2Nb3O10 nanocomposite detects nitrite linearly over a concentration range of 4.4 × 10−4 to 6.0 × 10−3 M.